Development of cryopreservation methods of seed of Nepeta cataria - Ishmuratova, M.Yu.; Baigarayev, D.S.; Tleukenova, S.U.; Gavrilkova, E.A.; Ramasanov, A.K.; Zhumina, A.G. (KU Publ., 2021)
This article presents the summarized data on cryopreservation of seeds of the medical plant Nepeta cataria. Cryopreservation is a highly promising method for saving of seed materials, allowing to organize long-term storage without viability loss. The purpose of present work is to optimize conditions of cryopreservation of seed materials of Nepeta cataria. Assessment of seed survival rate in the storage showed a linear decrease in seed viability and energy of germination. After 30 months of storage at the low positive temperature (+5 ºC) in paper pack seed rate decreased to 12.0 % and energy of germination to 11.2 %; after 4 years of storage seeds lost viability. During conduction of research the type of container, condition of thawing, optimal moisture of seeds and cryoprotectants are optimized. The optimal container for cryopreservation in liquid nitrogen was plastic cryo tubes; defrosting at room temperature. The best seed rate is found at moisture 3 %; the best cryoprotectant was glucose, the optimal concentration was 15 %. The result of the research is used for creation of the long-term storage medicinal cultures’ seed bank in the liquid nitrogen.
Nepeta cataria тұқымдарының криоконсервациялау әдісін әзірлеу
Разработка методов криоконсервации семян Nepeta cataria
Keywords: Nepeta cataria; medicinal plant; seed materials; germination; liquid nitrogen; cryo protectants; cryopreservation